2018
DOI: 10.1038/s41467-018-06924-5
|View full text |Cite
|
Sign up to set email alerts
|

SUMOylation of ROR-γt inhibits IL-17 expression and inflammation via HDAC2

Abstract: Dysregulated ROR-γt-mediated IL-17 transcription is central to the pathogenesis of several inflammatory disorders, yet the molecular mechanisms that govern the transcription factor activity of ROR-γt in the regulation of IL-17 are not fully defined. Here we show that SUMO-conjugating enzyme Ubc9 interacts with a conserved GKAE motif in ROR-γt to induce SUMOylation of ROR-γt and suppress IL-17 expression. Th17 cells expressing SUMOylation-defective ROR-γt are highly colitogenic upon transfer to Rag1–/– mice. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 38 publications
3
30
0
Order By: Relevance
“…These findings are supported by the essential role of class I HDACs, especially HDAC2, in inflammation: in the context of LPS induced inflammation, HDAC2 has been observed to down-regulate expression of IL-6 by recruitment to its promoter and subsequent deacetylation of H4 and H3 in myeloid cells (66). Similar regulatory functions were detected in chronic inflammatory disorders like rheumatoid arthritis or multiple sclerosis, in which dysregulation of the transcription factor RAR-related orphan receptor g has been described to result in HDAC2 recruitment to IL-17 promoter and its subsequent repression (67). Besides that, HDAC2 also exerts a particular role in the context of vascular inflammation.…”
Section: Discussionmentioning
confidence: 82%
“…These findings are supported by the essential role of class I HDACs, especially HDAC2, in inflammation: in the context of LPS induced inflammation, HDAC2 has been observed to down-regulate expression of IL-6 by recruitment to its promoter and subsequent deacetylation of H4 and H3 in myeloid cells (66). Similar regulatory functions were detected in chronic inflammatory disorders like rheumatoid arthritis or multiple sclerosis, in which dysregulation of the transcription factor RAR-related orphan receptor g has been described to result in HDAC2 recruitment to IL-17 promoter and its subsequent repression (67). Besides that, HDAC2 also exerts a particular role in the context of vascular inflammation.…”
Section: Discussionmentioning
confidence: 82%
“…Several studies have revealed that RORγt-de cient T cells show suppressed differentiation of Th17 cells and downregulate IL-17A, while overexpression of RORγt induces IL-17A expression, conversely [47]. In addition, Amir Kumar Singh et al elaborated a detailed mechanism that SUMOylation of RORγt promotes HDAC2 interaction with the IL-17 promoter and suppresses IL-17A transcription [33]. Furthermore, a research demonstrated RORγt acetylation in Th17 cells, with a signi cant enhancement by HDAC2 inhibitors [47], consistent with a recent study which revealed elevated RORγt acetylation in cultured CSEinduced HBE cells with HDAC2 silencing [22].…”
Section: Discussionmentioning
confidence: 99%
“…Decreased RORγt expression and Th17 response under CS and OVA challenge after CpG-ODN and BUD treatment HDAC2 is important in Th-17 cell differentiation from naive CD4 + T cells, and RORγt involvement attracts increasing attention [32,33]. The catalytic activity of HDAC2 is important in inhibiting RORγt's transcriptional activity, and SUMOylated RORγt recruits HDAC2 to the IL-17 promoter for gene downregulation [34].…”
Section: Alteration Of Th2/th17 Polarization and Reduction Of Pro-in mentioning
confidence: 99%
“…The silver stained gel slice was destained according to the manufacturer's protocol (PROTSIL2-1KT, Sigma). The digestion for gel slice, whole lysates and IPed beads were done according to previously published protocols (Singh et al 2018).…”
Section: Sample Digestion For Msmentioning
confidence: 99%
“…For DDA mode, the MS was set to collect one high-resolution MS1 scan (60,000 FWHM @200 m/z; scan range 400-1500 m/z) followed by data-dependent High-energy C-trap Dissociation MS/MS (HCD) spectra on the 20 most abundant ions observed in MS1. Other MS parameters were as previously published (Singh et al 2018).…”
Section: Liquid Chromatography Mass Spectrometry (Lc-ms/ms)mentioning
confidence: 99%